RAIN: ReseArch Infrastructure Network : A communication network for sending messages between research infrastructure in the Nordics - Lonie, Calum (Luleå tekniska universitet, Rymdteknik, 2024)
As scientific research plunges deeper into the depths of detail, a need for multi-instrument observations is growing. The history and range of research infrastructure available in the Arctic region of the Nordics represents an ideal target for multi-instrument observations, potentially allowing for observations to be made using different instrument types, in several locations, simultaneously. However, the existing infrastructure does not have sufficient integration to enable this. This project, undertaken as a Master's Thesis at IRF, aims to provide a solution to this problem. The result of this project is an open source software package, written in Python, entitled RAIN. RAIN allows research infrastructure to run a server, providing data, or a client, receiving this data, in a decentralised peer-to-peer network. The aim of this network is to allow servers and clients to send information to one another through the exchange of messages. Such a network was developed throughout this project and has resulted in an open source, lightweight, feature-complete and documented package. This package was successfully tested in a real-world scenario using an AllSky7 meteor camera placed on the roof at IRF. The RAIN software package is now available to install from PyPI and is licensed under the GNU General Public License v3.0